Modification of CaO Catalyst with Impregnation Method Using KoH in Biodiesel Synthesis from Waste Cooking Oil - Syarifuddin Oko; Andri Kurniawan (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
Chicken eggshells can be used as raw material in the manufacture of CaO catalysts. Increased CaO catalyst activity can be done by the impregnation method. The purpose of this study was to determine the effect of %K on the wet impregnation of CaO catalyst using KOH and to find out the impregnation catalyst (CaO / K2O) on the biodiesel yield. Prepared chicken egg shells were calcined at 900oC for 3 hours. Then the CaO obtained was impregnated using KOH with a variation of % K (5%, 7%, 9% and 12% (w / w)) while heated at 85oC. The impregnation product was calcined at 600oC for 5 hours. The impregnation catalyst (CaO K2O) was applied to the biodiesel synthesis through a transesterification reaction with a mole ratio of 1:12 waste cooking oil: methanol, the amount of catalyst was 1.5% at a reaction temperature of 70°C for 2.5 hours. Based on the results of SEM-EDS analysis, the highest K2O at 7% K was 21.99%), while the highest CaO content was at 9% K by 81.53%. For the highest surface area analysis at 7% K with a surface area of 71.22 m2 / g, alkalinity was 2.59 mmol / g. The best biodiesel was obtained with a yield of 87.17%, kinematic viscosity of 2.89 cSt, water content of 0.032%, density of 0.819 g/ml, methyl ester level of 99.39%.